Population, breeding and recruitment of Ganga river prawn Macrobrachium choprai - ., Sree Prakash (Indian Journal of Fisheries, 2011)
Studies were conducted on Macrobrachium choprai during 1983-86 in Gangetic stretch fromAllahabad to Bhagalpur. Monsoon, the breeding season, showed the highest catch and the cyclicalmovements were relatively unimportant. Practically 6 size groups were observed in the catches in boththe sexes but females perdominated during breeding period, the pre-and post-monsoon. Length-weightrelationship was governed by the cube law with modification and average growth rate was recorded tobe 4-6 mm/inonth. There were 6 stages of maturity presenting polymodal distribution in monthly ovadiameterpolygon. The first maturity was observed at 60 mm. Breeding, embryonic development andhatching occurred in freshwater and hatchlings swam away to esturine zone for larval development.They re-migrate upwards during autumn after attaining juvenile stage, for nursing and growth givinginceased abundance progressively downwards.